2014
DOI: 10.1002/app.40779
|View full text |Cite
|
Sign up to set email alerts
|

Influence of microwave heating time on the structure and properties of chitosan films

Abstract: The aim of this study was to investigate chitosan film behavior during microwave heating for 10 different heating times from 0 to 40 min. Chitosan films were produced by casting. Their structure and properties were investigated with several techniques, including Fourier transform infrared spectroscopy and differential scanning calorimetry, but also by the measurement of the film color and the mechanical properties or by the study of the rheological properties of the rehydrated films. An original technique of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 49 publications
(88 reference statements)
0
11
0
Order By: Relevance
“…In particular, it has thermoplastic characteristics that enable it to be processed easily, and it has been used as a very useful ingredient and additive in many industries . However, the physical properties of starch are worse than synthetic polymers, and it has some drawbacks, such as being highly hydrophilic, a poor water vapor barrier, and poor stability . These properties can be improved by physical, chemical, and enzyme modification methods .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In particular, it has thermoplastic characteristics that enable it to be processed easily, and it has been used as a very useful ingredient and additive in many industries . However, the physical properties of starch are worse than synthetic polymers, and it has some drawbacks, such as being highly hydrophilic, a poor water vapor barrier, and poor stability . These properties can be improved by physical, chemical, and enzyme modification methods .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown the mechanical properties and barrier properties of the edible films are improved by exposing samples to high temperatures . In addition, the film solution is more uniform and smooth with high rapid heating . Nowadays, ultrasonic/microwave‐assisted treatment is widely used in the extraction and synthesis of components, and it is beneficial for improving the properties of edible films .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, improvement of the performance of edible film via ultrasonic treatment has been demonstrated, e.g., enhanced intermolecular forces, formation of a dense structure, elimination of air bubbles and easy vacuum degassing (Wang et al 2014b). Microwaves offer a fast and convenient method for heating, resulting in the breakage of hydrogen bonds and strengthening of the intermolecular crosslinking interactions (Jacquot et al 2014). Currently, ultrasonic/microwave-assisted treatment is widely used in the extraction and synthesis of components, the advantages of the proposed method being high extraction efficiency and solvent-free extraction (Feng et al 2014), and rarely used to improve the performance of protein edible film (Wang et al 2014b).…”
Section: Introductionmentioning
confidence: 99%